Peran Crispr-Cas9 dalam Rekayasa Genetik Tomat (Solanum Lycopersicum) sebagai Upaya Peningkatan Ketahanan Pangan pada Bioteknologi Pertanian - Wahyuni, Sri; Hala, Yusminah (Jurnal Biosilampari : Jurnal Biologi, 2025)
This study aims to review various scientific publications related to the application of CRISPR-Cas9 in tomato genetic engineering to enhance food security. The research method used is a literature from reputable databases such as Scopus, ScienceDirect, and PubMed. The results show that CRISPR-Cas9 offers several advantages, including high specificity, multiplexing capability, and flexibility in genome editing. Its applications in tomatoes involve improving resistance to biotic stress (pathogens and diseases) and abiotic stress (drought, extreme temperatures), enhancing nutritional quality, extending fruit shelf life, and increasing productivity. These improvements are directly linked to food security by ensuring stable production, reducing postharvest losses, and increasing crop resilience to climate change. Therefore, CRISPR-Cas9 technology provides an innovative strategy for sustainable agricultural biotechnology development and global food security enhancement.